ETHANOL EXTRACT FORMULATION OF TUNJUK LANGIT RHIZOME AS TABLET BY WET GRANULATION METHOD - Fitrya A (Universitas Bhakti Kencana, 2016)
Tunjuk langit rhizome (Helminthostahcys zeylanica (Linn) Hook) has been used traditionally as an anticancer and antiinflammatory agent. Previous studies have proved the potency of ethanol extract from this rhizome as an antihyperuricemic agent. In this study, the ethanol extract of the rhizome, was formulated into tablet dosage forms by a wet granulation method. Three tablet formulas with different types of disintegrant and binder were formula A (starch: PVA), formula B (AvicelÂ®PH102: PVP), and formula C (sodium alginate: methylcellulose). Physical properties (such as weight variation, tablet diameter, thickness, friability, hardness, and disintegration time) and dissolution of tablets were evaluated. The analysis results showed that formula A produced the best physical properties and dissolution characteristics.